Depression prevention via digital cognitive behavioral therapy for insomnia: a randomized controlled trial. Issue 10 (17th September 2019) - Cheng, Philip; Kalmbach, David A; Tallent, Gabriel; Joseph, Christine Lm; Espie, Colin A; Drake, Christopher L
Abstract: Study Objectives: Insomnia is a common precursor to depression; yet, the potential for insomnia treatment to prevent depression has not been demonstrated. Cognitive behavioral therapy for insomnia (CBT-I) effectively reduces concurrent symptoms of insomnia and depression and can be delivered digitally (dCBT-I); however, it remains unclear whether treating insomnia leads to sustained reduction and prevention of depression. This randomized controlled trial examined the efficacy of dCBT-I in reducing and preventing depression over a 1-year follow-up period. Methods: Patients with Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition ( DSM -5) insomnia disorder were randomly assigned to receive dCBT-I or an attentional control. The follow-up sample included 358 patients in the dCBT-I condition and 300 patients in the online sleep education condition. The primary outcome measure was relative rate ratios for depression at 1-year follow-up. Insomnia responses to treatment were also tested as predictors of incident depression at the 1-year follow-up. Results: At 1-year follow-up, depression severity continued to be significantly lower in the dCBT-I condition relative to control. In addition, the number of individuals who reported no depression at 1-year follow-up was 51% higher in the dCBT-I condition relative to control. In those with minimal to no depression at baseline, the incident rate of moderate-to-severe depression at 1-year follow-up was reduced by half in the dCBT-I condition relative to the control condition. Conclusion: dCBT-I showed robust effects as an intervention that prevents depression. Future research should examine dose–response requirements and further characterize mechanisms of action of dCBT-I for depression prevention. Clinical Trial: Sleep to Prevent Evolving Affective Disorders; NCT02988375.